2011
DOI: 10.1901/jeab.2011.96-261
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Persistence of Treatment Effects During Long‐term Treatment of Destructive Behavior

Abstract: Eight young children who displayed destructive behavior maintained, at least in part, by negative reinforcement received long-term functional communication training (FCT). During FCT, the children completed a portion of a task and then touched a communication card attached to a microswitch to obtain brief breaks. Prior to and intermittently throughout FCT, extinction probes were conducted within a withdrawal design in which task completion, manding, and destructive behavior were placed on extinction to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
273
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(296 citation statements)
references
References 28 publications
17
273
6
Order By: Relevance
“…All participants engaged in the response paired with an increased response effort during extinction; interestingly, participants engaged in the increased response requirement (placing balls in a basket 1.829 m away) at lower rates during extinction when compared to participants exposed to a minimal response requirement (placing balls in a basket .9 m away). The findings of the current study are consistent with previous research on resurgence (e.g., Sweeney & Shahan, 2013;Wacker et al, 2013) and add to the growing research on mitigating rates of resurgence in clinical settings (e.g., Marsteller & St. Peter, 2014;Volkert et al, 2009). When taken together with the differentiation of rates of resurgence during periods of extinction, it would appear that response effort (rather than magnitude of reinforcement) diminished resurgence rates during phase III.…”
Section: Resultssupporting
confidence: 89%
“…All participants engaged in the response paired with an increased response effort during extinction; interestingly, participants engaged in the increased response requirement (placing balls in a basket 1.829 m away) at lower rates during extinction when compared to participants exposed to a minimal response requirement (placing balls in a basket .9 m away). The findings of the current study are consistent with previous research on resurgence (e.g., Sweeney & Shahan, 2013;Wacker et al, 2013) and add to the growing research on mitigating rates of resurgence in clinical settings (e.g., Marsteller & St. Peter, 2014;Volkert et al, 2009). When taken together with the differentiation of rates of resurgence during periods of extinction, it would appear that response effort (rather than magnitude of reinforcement) diminished resurgence rates during phase III.…”
Section: Resultssupporting
confidence: 89%
“…Only children who completed FA and were started in FCT were included in the current analysis. Information on a subsample of children from group 1 was reported previously by Wacker et al 12 Wacker et al 5,11 reported selected data from 20 of the participants from group 2, and Suess et al 14 described treatment fidelity data from the first 3 participants in group 3. Among the 107 children who started FCT in these 3 groups, 8 discontinued treatment in group 1 (3 with ASD, 5 with other DD), 3 discontinued treatment in group 2, and 2 discontinued treatment in group 3.…”
Section: Childrenmentioning
confidence: 99%
“…Wacker et al 5 demonstrated that weekly coaching for parents can identify the social functions of problem behavior and replace these behaviors with alternative communication. [11][12][13] In the initial studies in this series, 12,13 behavior consultants traveled to family homes weekly to coach parents in conducting FA and FCT. The same strategies have subsequently been tested via telehealth, initially by having families travel to outpatient clinics near their homes 5, 11 and later by providing telehealth coaching to parents in their own homes.…”
mentioning
confidence: 99%
“…Specifically, targeting varied mand responding during FCT may have utility in terms of the Implications for Practice • Extension of previous research on the use of FCT to treat challenging behavior exhibited by individuals with autism • Extension of previous research on the use of lag schedules to increase varied mand responding in individuals with autism • First investigation to evaluate the effects of combining lag schedules and FCT on varied mand usage during treatment of challenging behavior • Reinforcing mand variability may have utility in preventing or mitigiating clinical relapse of challenging behavior during challenges to treatment prevention or mitigation of clinical relapse (e.g., resurgence; Epstein, 1983). Wacker et al (2011) described several conditions that represent challenges to treatments that can result in the resurgence of challenging behavior including brief and/or prolonged periods of extinction of mands resulting from lapses in treatment fidelity. This effect has been demonstrated in several studies in which resurgence of challenging behavior occurred when extinction was applied to trained mands during FCT (e.g., Wacker et al, 2011).…”
mentioning
confidence: 99%